Design and Development of Interactive Learning Media to Increase Student Learning Interest - Rachmawaty, Rikeu; Sarmidi, Sarmidi; Muhammad, Taofik (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
This study aims to design interactive learning media for improving students' learning interest in computer systems material. The research employs Research and Development (R&D) methodology with the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Seventh-grade students at MTs Ar-Rahmah, Tasikmalaya City, participated as research subjects. Subject matter and media experts validated the interactive learning media, yielding validation results of 100% and 96% respectively, both categorized as